More Ads, More Viewers? Analyzing Behavioral Shifts from Advertising Permissions to Live Streaming Consumption - Wu, Michael W.; Ham, Sung H. (Journal of Marketing, 2026)
There has been little exploration of how audience content consumption may change in response to advertising permissions on live streaming platforms. Brands use ads to generate revenue through ad exposure, but is this benefit thwarted by the reduction of audience consumption of content? Using a dataset containing over 12 million observations in the live streaming space and a difference-in-differences estimation approach, the authors study the effects of a policy intervention by a live streaming platform that provided (some) streamers the ability to display midroll advertisements. Although the ad avoidance literature infers that audiences view ad-supported content unfavorably, the results of this study indicate that providing the mere ability to introduce midroll advertisements has a notable positive effect on live streaming content consumption (average viewership and total hours watched). The authors discover that a viable explanation for this response is through increases in broadcasting airtime, stream frequency (somewhat), and quality by streamers after the intervention, as these adjustments are drastically easier to implement in a live streaming setting than in more traditional forms of media. The authors further explore heterogeneity in these effects in relation to initial streamer success, streaming tenure, content activity, culture (of the streamer and audience), and impact across time.